Ambos sexos de Scyphophorus acupunctatus (Coleoptera: Dryophthoridae) pueden iniciar la colonización de la planta de agave (Asparagaceae)/Both sexes of Scyphophorus acupunctatus (Coleoptera: Dryophthoridae) can start the colonization of the agave plant (Asparagaceae) - Figueroa-Castro, Pedro; González-Hernández, Héctor; Carrillo-Sánchez, José Luis; Del Reallaborde, José Ignacio; Solís-Aguilar, Juan Fernando; Rojas, Julio C. (Instituto de Ecología, A.C., 2015)
This study was conducted for determining the pioneer sex of agave weevil on agave plants. Field experiments were made on plantations of Agave tequilana Weber var. Azul in Jalisco, and Agave angustifolia Haw. and Agave cupreata Trel. & Berger in Guerrero. It was found that both sexes were able to start colonizing agave host plants. Most of the females that colonized host plants were gravid.